Experimental Study of Brain Activity on ECVT-Based Motor Movements - Hani Nur Endah; Heni Sumarti; Marlin Ramadhan Baidillah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
This study investigates the characterization of brain signals in response to motor stimulation using the principle of Electrical Capacitance Volume Tomography (ECVT). The experiment was conducted on a 21-year-old male subject, who was exposed to motor tasks (hand gripping and imagined movement) and audiovisual stimulation (watching a film), alongside control conditions with water and air. Data acquisition was performed using an ECVT helmet sensor at frequencies of 500 kHz, 1 MHz, and 5 MHz. The results revealed variations in vpp values across different conditions, with the highest sensitivity observed at 500 kHz during imagined movement. These findings indicate that internal motor imagery elicits stronger brain activity compared to resting or external stimulation. Overall, the study demonstrates that ECVT is capable of distinguishing brain signal characteristics under different types of stimulation, with 500 kHz identified as the optimal frequency for sensitivity.